The preacher and the presidents : Billy Graham in the White House - Gibbs, Nancy, 1960-; Duffy, Michael, 1958- (New York, NY : Center Street, 2008)
No one man or woman has ever been in a position to see the presidents, and the presidency, so intimately, over so many years. They called him in for photo opportunities. They called for comfort. They asked about death and salvation; about sin and forgiveness. At a time when the nation is increasingly split over the place of religion in public life, this book reveals how the world's most powerful men and world's most famous evangelist, Billy Graham, knit faith and politics together.--From publisher description.
Includes bibliographical references and index.
Keywords: Graham, Billy, -- 1918-2018.; Presidents -- United States -- Religion; Christianity and politics -- United States